E-001 Comparison of Clinical Outcomes in Patients with Anterior Circulation Acute Ischemic Strokes Treated with Mechanical Thrombectomy using the ADAPT Technique Only versus ADAPT with Solumbra Salvage. (29th July 2016) - Delgado Almandoz, J; Kayan, Y; Young, M; Fease, J; Scholz, J; Milner, A; Roohani, P; Hehr, T; Mulder, M; Tarrel, R
Abstract : Purpose: To compare procedural and clinical outcomes in patients with anterior circulation acute ischemic strokes treated with mechanical thrombectomy using ADAPT technique only or ADAPT with Solumbra salvage. Materials and methods: We restrospectively reviewed a consecutive cohort of patients with anterior circulation acute ischemic strokes treated with mechanical thrombectomy using ADAPT technique only or ADAPT with Solumbra salvage at our institution between March 11th, 2013 and December 31st, 2015. Baseline clinical and radiological characteristics and procedural variables were recorded. Clinical outcomes at 90 days were recorded using the modified Rankin Scale (mRS). Results: Fifty-nine patients were included, 33 male (56%). Mean age 67.1 years, mean admission NIHSS 19.1. Forty-six patients were treated with ADAPT only (78%) and 13 with ADAPT with Solumbra salvage (22%). Table 1 summarizes baseline clinical and radiological characteristics. There was a trend towards a higher proportion of patients with ICA terminus thrombi in the ADAPT with Solumbra salvage group (69.2%, p-value 0.054). Table 2 summarizes the procedural variables. There was a significantly-lower mean time from puncture to reperfusion in the ADAPT only group (29.5 minutes) compared to the ADAPT with Solumbra salvage group (85.1 minutes, p-value < 0.001). There was a significantly-higher number of mean thrombectomy device passes in the ADAPT with Solumbra salvage group (5.6) compared to the ADAPT only group (2.3, p-value 0.005). There are a significantly-higher rate of iatrogenic cervical vascular dissection in the ADAPT with Solumbra salvage group (15%) compared to the ADAPT only group (0, p-value 0.046). Table 3 summarizes the clinical outcomes. There was a significantly-higher rate of unfavorable clinical outcome (mRS 4–6) and death at 90 days in the ADAPT with Solumbra salvage group (61.5% and 38.5%, respectively) compared to the ADAPT only group (28.3% and 10.9%, p-value 0.047 and 0.033, respectively). There was a trend towards a higher rate of favorable clinical outcomes (mRS 0–2) at 90 days in the ADAPT only group (54%) compared to the ADAPT with Solumbra salvage group (31%, p-value 0.21). Conclusion: Among patients treated with mechanical thrombectomy using an ADAPT-first approach, those requiring Solumbra salvage had significantly-higher rates of unfavorable clinical outcome and death at 90 days. Disclosures: J. Delgado Almandoz: 2; C; Medtronic Neurovascular, Penumbra, Inc. Y. Kayan: 2; C; Medtronic Neurovascular, Penumbra, Inc. M. Young: None. J. Fease: None. J. Scholz: None. A. Milner: None. P. Roohani: None. T. Hehr: None. M. Mulder: None. R. Tarrel: None.